Analysis of the Prophetic Leadership Management Model in Strengthening Teachers’ Spiritual Values and Performance - Aliftia Nabilah Salma; Nurodin Usman (Universitas Wahid Hasyim Semarang, 2026)
This study aims to analyze prophetic leadership management to develop spiritual values ​​and teacher performance in leading Islamic schools in Muntilan District, Magelang Regency, namely SMP Muhammadiyah Plus Gunungpring and SMP Muhammadiyah Muntilan. This is a qualitative descriptive study to analyze the functions of leadership management, consisting of planning, organizing, implementing, and controlling. Data collection was conducted through observation, interviews, and documentation. The data obtained were tested for validity through triangulation of techniques and sources. Data analysis techniques included data presentation, data reduction, and concluding. The results concluded that the implementation of prophetic leadership in the research subjects was effective. Management practices in the research subjects have internalized the four main dimensions of the Prophet Muhammad's leadership: shiddiq, amanah, tabligh, and fathanah. The analysis shows that the implementation of prophetic leadership can improve spiritual values ​​and teacher performance. Improving spiritual values ​​and teacher performance will encourage a paradigm shift in learning from simply transferring knowledge to building student character. Good teacher performance can also strengthen exemplary values ​​in the learning process. The analysis is expected to positively impact teacher performance through the implementation of spiritual values ​​derived from the prophetic leadership management model. The novelty of this research lies in the importance of the prophetic leadership model for strengthening spiritual values ​​and teacher performance in schools based on religious organizations in Indonesia.